2013
DOI: 10.4038/jnsfsr.v41i4.6257
|View full text |Cite
|
Sign up to set email alerts
|

Storage and germination treatments for seeds of an ornamentally important palm, Livistona rotundifolia (Lam.) Mart.

Abstract: Livistona rotundifolia (Lam.) Mart. is an ornamentally important plant in Sri Lanka with a high demand for both cut foliage and pot plant production for the foreign market. Propagation through seeds, poor germination and the storage of seeds are the main constraints in L. rotundifolia cultivation. During the current study, seed germination and storage behaviour of L. rotundifolia have been investigated to identify the causes for its poor germination and poor storability. The moisture content of seeds was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Given these results, the species can be characterized as neutral photoblastic, because, in addition to having greater germination capacity in the dark, the seeds also germinate in the presence of light. This condition of neutral photoblastism is not a rule for family Arecaceae, because Sanjeewani et al (2013) observed that Livistona rotundifolia (Lam.) Mart, a species that also belongs to this family, only germinated in the absence of light, after 30 days of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these results, the species can be characterized as neutral photoblastic, because, in addition to having greater germination capacity in the dark, the seeds also germinate in the presence of light. This condition of neutral photoblastism is not a rule for family Arecaceae, because Sanjeewani et al (2013) observed that Livistona rotundifolia (Lam.) Mart, a species that also belongs to this family, only germinated in the absence of light, after 30 days of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to dormancy, there are other variables that affect seed germination, such as light and temperature. Regarding family Arecaceae, temperature and light variation have already been studied by different authors, which determined what conditions result in the best germination potential for these species (Pérez et al, 2008;Pimenta et al, 2010;Ribeiro et al, 2011;Sanjeewani et al, 2013;Rodrigues et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Petri dishes were randomly distributed in temperature-controlled incubators and their position was changed daily. Germination was defined as the first emergence of the radicle (Sanjeewani et al, 2014). Newly-germinated seeds were counted each day for 30 d and subsequently removed from the Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…The inflorescence is a panicle of small yellowish flowers followed by clusters of yellow fruits, ripening to orange-red to red or to dark violet or black (DOWE, 2009). Seeds are recalcitrant, exhibit a low embryo: seed ratio, require darkness for germination, and show a slight non-deep physiological dormancy (SANJEEWANI et al, 2013). As stated by Viana et al (2013), pulp removal increases germination rate whereas seed storage decreases the percentage of germinated seeds.…”
Section: Introductionmentioning
confidence: 98%